Inferior frontal gyrus preserves working memory and emotional learning under conditions of impaired noradrenergic signaling - Becker, Benjamin; Androsch, Lucas; Jahn, Ralph T.; Alich, Therese; Striepens, Nadine; Markett, Sebastian; Maier, Wolfgang; Hurlemann, René (Frontiers in Behavioral Neuroscience, 2013)
Compensation has been widely applied to explain neuroimaging findings in neuropsychiatric patients. Functional compensation is often invoked when patients display equal performance and increased neural activity in comparison to healthy controls. According to the compensatory hypothesis increased activity allows the brain to maintain cognitive performance despite underlying neuropathological changes. Due to methodological and pathology-related issues, however, the functional relevance of the increased activity and the specific brain regions involved in the compensatory response remain unclear. An experimental approach that allows a transient induction of compensatory responses in the healthy brain could help to overcome these issues. To this end we used the nonselective beta-blocker propranolol to pharmacologically induce sub-optimal noradrenergic signaling in healthy participants. In two independent fMRI experiments participants received either placebo or propranolol before they underwent a cognitive challenge (experiment 1: working memory; experiment 2: emotional learning: Pavlovian fear conditioning). In experiment 1 propranolol had no effects on working memory performance, but evoked stronger activity in the left inferior frontal gyrus (IFG). In experiment 2 propranolol produced no effects on emotional memory formation, but evoked stronger activity in the right IFG. The present finding that sub-optimal beta-adrenergic signaling did not disrupt performance and concomitantly increased IFG activity is consistent with, and extends, current perspectives on functional compensation. Together, our findings suggest that under conditions of impaired noradrenergic signaling, heightened activity in brain regions located within the cognitive control network, particularly the IFG, may reflect compensatory operations subserving the maintenance of behavioral performance.